Prospects for using remote sensing data in the armed forces, other troops and military formations of the Republic of Kazakhstan - Zakiev, Erlan S.; Kozhakhmetov, Serikhan K. (Vojnotehnički glasnik / Military Technical Courier, 2021)
Introduction/aim: This article is written to acquaint readers with the development of a space system of Earth remote sensing in the Republic of Kazakhstan using remote sensing data to support the Armed Forces, other troops and military formations of the Republic of Kazakhstan. Methods: An analytical approach to the study of the development of space and information technologies has led to qualitative changes in the field of remote sensing of the Earth. Conclusions were also made based on the analysis of the historical aspects of the formation and development of space systems for remote sensing of the Earth. This article deals with significant improvements in the field of geoinformation support to the Armed Forces, other troops and military formations in the interests of the security of the Republic of Kazakhstan using high-resolution satellite images from domestic spacecraft to create digital state topographic maps of the entire scale series with simultaneous updating. Results: The article provides a brief overview of remote sensing systems using geoinformation technologies in foreign countries and in the Republic of Kazakhstan. Conclusions: A special unit "Photogrammetric center for remote sensing and UAV data processing" is capable of processing data of remote sensing and UAVS for the armed forces, other troops and military units of the Republic of Kazakhstan. Data processing technologies have little in common with traditional processing and representation of geographical data, and finally, geographical data serves only as a basis for solving a large number of applied problems.